Enhancing public speaking confidence, skills, and performance: An experiment of service-learning. Issue 2 (July 2019) - McNatt, D. Brian
Abstract: Much of service-learning research has been characterized as anecdotal and testimonial with widespread calls for more empirical data to support the claimed benefits of this pedagogical tool. The present longitudinal experiment answered these calls by testing the effect of service-learning projects on several oral communication skills during a 4-month period, as well as some boundary conditions affecting this impact. The intervention consisted of involvement in 1 of 20 different team-developed service-learning projects compared to traditional research projects. This was hypothesized to boost management students' public speaking self-efficacy, lower anxiety, and improve public speaking mechanics competence along with actual public speaking performance (evaluated by independent raters). Results indicated that a wide array of service-learning projects can positively impact students in each of these important areas of public speaking. It was also found that service-learning more strongly benefited those initially lower in public speaking self-efficacy. Thus, this experiment suggests that instructors can include a service-learning component in their courses that can aid students' oral communication skill development. Highlights: Service-learning projects improve public speaking self-efficacy and performance. Service-learning experience can decrease students' public speaking anxiety. Service-learning gains are greater with students with initial low self-efficacy. Many kinds of service-learning projects can produce public-speaking improvements.